If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c = 6 Solving 6c = 6 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '6'. c = 1 Simplifying c = 1
| -2(3y-1)-x=0 | | x^3=-10x^2-24x | | 24(y+2)=45 | | 7r-30=5 | | 96+2a=a+101 | | 8x+(3+7x)= | | 8c+(7-9c)= | | x^2-2x=80 | | x^2+34x=0 | | 9c=36 | | 0.5x+0.4(20)=0.3(x+30) | | x^2+50x=0 | | -2a+3+3a=11-20 | | w-4w+20=-8 | | x(x+7)=-12 | | 3(x+1)-1=3x+2 | | 3x^2-13x=-4 | | x^2+48=0 | | 5(5y-2)-4(4y-3)=y | | 2x(x+6)-10=55 | | 2(2w+8)+2w=76 | | 8y+3y+36=124 | | 4k=16 | | 7(b+3)=4b+2 | | w^2-3w=0 | | 8=4v+13 | | 7(b+3)=13b+2 | | x=3y-27 | | 10x^2+17x+7= | | n+n=20 | | 1.3(X+5)=10 | | 3n+2n=20 |